2002
DOI: 10.1017/s1074070800009305
|View full text |Cite
|
Sign up to set email alerts
|

Visitor Preferences and Values for Water-Based Recreation: A Case Study of the Ocala National Forest

Abstract: We used the open-ended contingent valuation method to elicit willingness to pay (WTP) for day visitors and extended visitors on the Ocala National Forest (ONF), Florida. A Tobit model specification was applied to account for the issues involved with censored WTP bids. The results reveal that visitors would pay more for improved recreational facilities at the ONF. In particular, our estimates show that visitors would pay $1 million for basic facilities, $1.9 million for moderate improvements, and $2.5 million f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
2
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 12 publications
1
11
2
1
Order By: Relevance
“…The mean number of trips, total travel cost, and household income were 2.36, $147.11, and $57,761, respectively (Rows 1 to 3, Table 3). 10 Most of the respondents (i.e., 79%) indicated that they had alternatives for similar recreation activities if the spring they visited was closed.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The mean number of trips, total travel cost, and household income were 2.36, $147.11, and $57,761, respectively (Rows 1 to 3, Table 3). 10 Most of the respondents (i.e., 79%) indicated that they had alternatives for similar recreation activities if the spring they visited was closed.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, those whose primary purpose was not for recreation in the springs were excluded, and those with highly frequent visits (above 95 percentile) were dropped to decrease the influences of extreme values. 10 Household income was a categorical response. Following previous studies, we used the mid-points of the categorical responses as the level of household income.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations